Young adults with ischemic stroke in the upper part section of Firat river - Demir, Caner F.; Berilgen, M. Said; Bulut, Serpil; Uelger, Meliha Aydin; Oezel, Seda (Ortadogu Ad Pres & Publ Co, 2007)
Stroke is one of the most important diseases causing severe disability and death. The incidence of ischemic stroke increases by age. Since the life expectancy is longer among the young population with stroke and due to economic and social challenges, research has focused on the causes of the disease. This study was planned to define the etiologic factors for stroke among young adults. Patients who had referred to the Firat University Firat Medical Center between March 2004 and March 2005 and were diagnosed as ischemic stroke were included. The ages of the patients were between 17 and 45. A detailed medical history was taken including personal and family history and risk factors and a detailed neurological evaluation was performed. Computed tomography (CT), magnetic resonance (MR) imaging, Doppler USG examination of the carotid and vertebral arteries, cardiac investigations, and detailed laboratory investigations were carried out for each patient. Of the 32 patients, 14 (43.8%) were males and 18 (56.2%) were females. The factors described for the etiology of stroke were atherothrombotic vasculopathy in 9 (28%) cases, emboli originating from the heart in 7 (21.9%), hematological disorders in 6 (19%), non-atherosclerotic vasculopathies in 5 (15.6%), other determined causes in 6 (18.8%), undetermined causes in 4 (12.5%), and lacunar stroke in 1 (0.3%). The most common risk factors for the etiology of young-age stroke are reported as atherothrombotic vasculopathy, non-atherosclerotic vasculopathies, and emboli originating from the heart. Similarly, in our study, vasculopathies were the most common causes followed by cardioembolic events and other determined causes. Stroke is an important neurological disease with regard to preventable risk factors at young age. Studies carried out for the prevention of conditions that cause stroke with a high risk of neurological deficits will be of great benefit for the young population, which make up the most active group of socio-economic life.
Keywords: cerebrovascular accident; youth